Removal of 2‐Rod Subdermal Implant Identified on X‐Ray: A Case Report - Laura C. D. Pomatto‐Watson; Julia Hutchison; Justin T. Hutchison (Clinical Case Reports)
ABSTRACT Case report of a 37‐year‐old Colombian patient seeking removal of a subdermal implant, initially believed to be the single‐rod Nexplanon implant. However, following extraction, it was identified as the 2‐rod international subdermal implant alternative, Jadelle. This case highlights the need for US health care providers to be cognizant of non‐US subdermal alternatives given the rising presence of foreign‐born patients they may encounter in their practice.